2023
DOI: 10.3390/horticulturae9050546
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Nutraceutical Characterization of Different Accessions of the Apricot (Prunus armeniaca L.)

Abstract: The name “Vesuvian apricot” refers to numerous varieties originating from the same production area at the foot of Vesuvius and with a long tradition of cultivation. The importance of the apricot fruit and its derivatives on human health is known thanks to the presence of several secondary metabolites, many of them being active as antioxidants. This study aims to analyze 12 vesuvian apricot accessions by means of chemical-physical (fruits weights, firmness, TSS, TA, pH, and color fruits) and nutraceutical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
1
2
1
Order By: Relevance
“…'Boriss' apricot fruit having the lowest (Figure 4A). The observed values are inconsistent with those reported by Cirillo et al [31] for 12 Vesuvian apricot accessions. The decrease in the content of hydrophilic and lipophilic antioxidants resulted in weak AOA of the elaborated DCF products.…”
Section: The Antioxidant Activity Of Apricot Fruit and Its Candied Pr...contrasting
confidence: 99%
See 2 more Smart Citations
“…'Boriss' apricot fruit having the lowest (Figure 4A). The observed values are inconsistent with those reported by Cirillo et al [31] for 12 Vesuvian apricot accessions. The decrease in the content of hydrophilic and lipophilic antioxidants resulted in weak AOA of the elaborated DCF products.…”
Section: The Antioxidant Activity Of Apricot Fruit and Its Candied Pr...contrasting
confidence: 99%
“…In this instance, differences in TSS are primarily due to the genetic background of apricot cultivars and, to a lesser extent, the maturity stage. The content of TSS in selected apricot cultivars is substantially lower than that reported by Cirillo et al [31] for apricot cultivars grown under Southern conditions and consistent with those of Rampáčková et al [32] reported for apricot cultivars originating from Central Europe, Central Asia, and the USA. Analyzing the TSS of developed DCF products, a statistically higher (p < 0.05) amount was found in cv.…”
Section: Physical-chemical Characteristics Of Apricot Fruit and Its C...supporting
confidence: 89%
See 1 more Smart Citation
“…sibirica, and kernel consumption apricots which are widely distributed in northern China [5]. The fruits of P. armeniaca are fresh with unique aroma, delicious taste, but also contains a variety of organic components, vitamins and inorganic salts, high nutritional value, wide range of uses, and can be processed into dried apricots, cultivated around the world, accounting for a high proportion of global fruit production [6,7]. P. sibirica has high ecological value as a pioneer tree species for vegetation restoration because it is cold, drought, and poor-soil tolerant.…”
Section: Introductionmentioning
confidence: 99%